2016
DOI: 10.1587/transinf.2016slp0013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Combining Various Major Language Model Technologies including Data Expansion and Adaptation

Abstract: SUMMARYThis paper aims to investigate the performance improvements made possible by combining various major language model (LM) technologies together and to reveal the interactions between LM technologies in spontaneous automatic speech recognition tasks. While it is clear that recent practical LMs have several problems, isolated use of major LM technologies does not appear to offer sufficient performance. In consideration of this fact, combining various LM technologies has been also examined. However, previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Results obtained with LSTM-RNN-LMs are shown in lines (2) and 3, and those obtained with RA-LSTM-RNN-LMs are shown in lines (4) and (5). They show that (3) outperformed (1) and (2), and (5) outperformed (3) and (4). This indicates that neural LMs can be complemented with the n-gram LM.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Results obtained with LSTM-RNN-LMs are shown in lines (2) and 3, and those obtained with RA-LSTM-RNN-LMs are shown in lines (4) and (5). They show that (3) outperformed (1) and (2), and (5) outperformed (3) and (4). This indicates that neural LMs can be complemented with the n-gram LM.…”
Section: Resultsmentioning
confidence: 84%
“…A lot of studies have been reported for improving language modeling in single speaker tasks. For a while, smoothed n-gram LMs were employed in ASR because they yield powerful performance in spite of simple modeling [1][2][3][4]. In recent studies, neural LMs that capture words by converting continuous representations have attracted a lot of attention [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The deep neural network is likely to be prone to over-fitting when the training dataset is small. Therefore, data expansion technology 24 is adopted to realize the expansion of the dataset for the original defect dataset (Figure 3). According to the characteristics of the image, more than one defect is observed in an image.…”
Section: Datasetmentioning
confidence: 99%
“…In addition, ASR systems consider only short context information when calculating the generative probabilities of words because they often use a traditional n-gram language modeling. In order to mitigate these problems, several techniques have been proposed [1]- [3]. In particular, approaches intended to improve LM structure have been aggressively pursued.…”
Section: Overviewmentioning
confidence: 99%